Non-coding RNAs in Necrotizing Enterocolitis- A New Frontier? - Nair, Jayasree; Maheshwari, Akhil (Current Pediatric Reviews, 2022)
With the recognition that only 2% of the human genome encodes for a protein, a large part of the “non-coding” portion is now being evaluated for a regulatory role in cellular processes. These non-coding RNAs (ncRNAs) are subdivided based on the size of the nucleotide transcript into microRNAs (miRNAs) and long non-coding RNAs (lncRNAs), but most of our attention has been focused on the role of microRNAs (miRNAs) in human health and disease. Necrotizing enterocolitis (NEC), an inflammatory bowel necrosis affecting preterm infants, has a multifactorial, unclear etiopathogenesis, and we have no specific biomarkers for diagnosis or the impact of directed therapies. The information on ncRNAs, in general, and particularly in NEC, is limited. Increasing information from other inflammatory bowel disorders suggests that these transcripts may play an important role in intestinal inflammation. Here, we review ncRNAs for definitions, classifications, and possible roles in prematurity and NEC using some preliminary information from our studies and from an extensive literature search in multiple databases including PubMed, EMBASE, and Science Direct. miRNAs will be described in another manuscript in this series, hence in this manuscript we mainly focus on lncRNAs.
Keywords: lncRNA